Measurements to design a coverage area by using high altitude platform systems - Riyam Alaa Johni (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper proposes the principles of how to design UMTS coverage area for Baghdad city the capital of Iraq country that occupy space about 204.2 km², by using new and promising technology for providing wireless narrowband and broadband telecommunication services as well as broadcasting services with either airships or airplanes which is named HAPs, Viewed from its altitude, HAPs floats within the stratosphere layer in the airspace, positioned between satellite and terrestrial platforms.this study also consider the affect of interference with the current broadband technology It will start with brief introduction for HAPS with its advantages, comparison between HAPS system and other services and specify requirements for design. Such as, enumerate the center of coverage area to find the coordinates. Then, supposed the coverage area for the city, and find the radius, elevation angle, and the location of earth stations which will connect HAPS with other networks and all other services location depending on latitude and longitude, finally the reduction of interference technique.